URGENSI DIGITAL LIBRARY DALAM PEMBERDAYAAN MADRASAH: Penggunaan Maktabah Syamilah versi 2.11 Dalam Peningkatan Kualitas Pembelajaran Guru di MAN 1 Model Bandar Lampung - Abdul Malik Ghozali (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
Madrasah is an Islamic educational institution that has a big role in development in the country. However, there are still some obstacles in his journey, including the lack of knowledge of teachers in the use of technology in learning such as the use of digital libraries. In this paper describes the efforts of MAN 1 Bandar Lampung in empowering the madrasah and the effectiveness of digital libraries in empowering the madrasah. The results of this research are: first, empowerment conducted in MAN 1 Bandar Lampung through several stages, awareness or enlightenment, intensive capacity and empowerment. Secondly, there are some improvement of teachers skill in the use of digital library, such as in searching verses of Koran and His commentary, referring some Hadith of the Prophet and his explanatory, seeking references for strengthening the subjects in the class, discussing problem solving and reviewing Arabic Grammar and Arabic Sciences.المدرسة هي مؤسسة تعليمية إسلامية لها دور كبير في التنمية في البلاد. ومع ذلك، لا تزال هناك بعض العقبات في رحلتها، بما في ذلك عدم معرفة المعلمين في استخدام التكنولوجيا في التدريس مثل استخدام المكتبات الرقمية. في هذه الورقة تصف جهود المدرسة الثنوية الحكومية النموذجية الأولى بندر لامبونج في تفعيل القوى المدرسية وفعالية المكتبات الرقمية في تفعيل المدرسة.  ونتائج هذا البحث هي: أولا، التفعيل الذي أجري في المدرسة الثنوية الحكومية النموذجية الأولى بندر لامبونج من خلال عدة مراحل، وهي التوعية أو التنوير، وتكثيف القدرات والتفعيل. وثانيا، هناك بعض الترقيات لقدرة المعلمين في استخدام المكتبة الرقمية، كما هو الحال في البحث عن آيات من القرآن الكريم وتفسيرها، وتخريج الأحاديث النبوية وشرحها، والحصول على مجموعة المراجع لتعزيز المواد الدراسية المدروسة في الصف، ومناقشة بحث المسائل ودراسة النحو والصرف والعلوم العربية.